DETERMINATION OF TECHNOLOGICAL PROBLEMS OF PROFILE GEAR GRINDING PRECISION CONTROL (Conferencea, 2023)
The article considers one of the factors influencing the process of processing kinematic threads and contributing to the reduction of the error in the manufacture of threads - the value of the allowance to be removed. Basically, we will talk about the allowance for final processing, where all accuracy parameters must be observed.